Holocene Climatic Change and Landscape Response at Cathedral Provincial Park, British Columbia, Canada - Heinrichs, Markus; Evans, Martin; Hebda, Richard; Walker, Ian; Palmer, Samantha; Rosenberg, Sandra (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractEnvironmental sensitivity to temperature change was established by comparing pollen, plant macrofossils, macroscopic charcoal, and sediment yield data from Lake of the Woods, Cathedral Provincial Park in the Cascade Mountains of southern British Columbia, Canada, to an independent record of midge-inferred paleotemperature. Steppe vegetation with some spruce and fir occurred initially, developing into pine forests in the warm early Holocene. These forests burned often, preventing spruce and fir succession. Once established, the forests retained an Engelmann Spruce-Subalpine Fir character. After 8000 cal BP, in warm but wetter conditions, the forest contained less pine and fires burned less frequently. About 4000 cal BP, cooler temperatures resulted in closure of the Engelmann Spruce-Subalpine Fir forests and a further reduction in fire frequency. Sediment yield results suggest a stable environment throughout the Holocene, likely due to sediment trapping in two upstream lakes. Midge-inferred temperatures correspond closely with a consensus reconstruction of temperatures from southern British Columbia, however Cathedral Provincial Park terrestrial ecosystems were not as sensitive to past climate change when compared to other nearby Engelmann Spruce-Subalpine Fir sites.